Hubungan Antara Beban Kerja dan Tingkat Pemahaman Perawat Mengenai Jangka Waktu Pengembalian Dokumen Rekam Medis Dengan Keterlambatan Pengembalian Dokumen Rekam Medis - Muhammad Amrullah; Teguh Achmalona; Suswinda Yuli Sutomo (STIKES Citra Delima Bangka Belitung, 2021)
Medical record documents are a source of providing patient medical information. Good medical record management, if the documents are accurate, complete, valid and on time for return. The purpose of this study was to find the relationship between workload and the level of understanding of nurses regarding the period of returning medical record documents with the delay in returning medical record documents at the Yatofa Islamic Hospital. The research method used is descriptive quantitative with cross sectional approach. The sampling process used total sampling technique, amounting to 65 people. The data collection technique used a questionnaire sheet. The data were analyzed using the chi square statistical test. The result of statistical test of workload variable obtained p value = 0.000 which is smaller than α = 0.05, indicating that there is a significant relationship between workload and delay in returning medical record documents. Whereas for the level of understanding variable, it was obtained that p value = 0.005 was smaller than α = 0.05, indicating that there was a relationship between the level of understanding and the delay in returning medical record documents. The delay in returning medical record documents is due to the high workload of nurses and the level of understanding of nurses regarding the period of returning medical record documents which is still lacking. This must be considered in order to support the implementation of efforts to improve the management of medical records that are good and can be held accountable by related parties.